Note sul "Verstehen": tra Dilthey e Weber - Franco Cambi (Firenze University Press, 2022)
aThe article deals with the debate on "understanding" that the German historicism developed during Nineteenth Century, the "school of Baden" and Max Weber. The text describes and analyzes the complex adventure that, for various reasons, affirmed the fundamental value of this cognitive category.